The effect of crop rotations and mineral fertilizers on economic and energy efficiency indicators when cultivating winter wheat in the Central Blackearth region - V. A. Lukyanov; L. B. Nitchenko (Зерновое хозяйство России)
Economic efficiency is an integral method of analyzing agricultural technologies, especially against the rising prices for plant protection products, seeds, fertilizers, and fuels and lubricants. Identification and implementation of the most effective methods of field crops, growing using crop rotation and fertilizers remains an urgent task.   The purpose of the current research was to study the effect of crop rotations and doses of mineral fertilizers on productivity of winter wheat grain, to analyze the economic and energy efficiency of its cultivation in the conditions of the Central Blackearth region.   The study was carried out in the conditions of the experimental field of the Federal Agricultural Kursk Research Center in 2016, 2020. The soil of the experimental plot was typical medium-loamy, medium-humus blackearth (chernozem). The experimental scheme included such factors as grain-fallow-row crop, grain-grass-row crop, and grain-grass rotations; with doses of fertilizers or without fertilizers, N20P40K40 and N40P80K80. The weather conditions for the rotations of the studied crop rotations differed slightly. As a result of the study, there was found that winter wheat grain productivity in grain-grass and grain-grass-row crop rotations was 17.2 and 13.8 % lower than in grain-fallow-row crop rotation. When applying mineral fertilizers at a dose of N40P80K80, the largest winter wheat productivity was 4.52 t/ha. The lowest cost of grain was established in the grain-fallow-row crop rotation, which varied from 4.68 to 5.04 thousand rubles/t due to higher yields compared to other studied crop rotations and with a dose of N20P40K40 (4.68, 4.80 and 4.97 thousand rubles/t, respectively for crop rotations). A higher level of profitability of 113.7 % was observed in grain-fallow-row crop rotation with a dose of mineral fertilizers N20P40K40, a dose of N40P80K80 not allowing obtaining a high payback of fertilizers. The energy intensity of production increased with increasing doses of applied fertilizers; its minimum values were determined in grain-fallow-row crop rotation (1.35–2.77 GJ/t). Energy efficiency coefficients when applying a dose of N20P40K40 in crop rotations were higher than when applying N40P80K80.